The competencies of social and emotional learning and their relationship to future skills among mathematics teachers in North Sharqiyah Governorate, Sultanate of Oman from their point of view - Al-Matari, Ali Said Sulaiyam; Al-Noumani, Shamsa Mohamed Rashid (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the competencies of social and emotional learning and their relationship to future skills among mathematics teachers in North Sharqiyah Governorate, Sultanate of Oman from their point of view, and the researchers used the descriptive analytical survey method, and the two study tools consisted of two questionnaires, the identification of cooperative competencies for academic, social and emotional learning)CASEL(2021, and the identification of future skills according to the Omani National Framework for Future Skills (2021).The study sample consisted of (51) teachers, and the results of the study showed that the total degree of availability of social and emotional learning competencies for mathematics teachers was average, with an arithmetic average of (2.71 out of(4 and at the level of sub-competencies, relationship skills and responsible decision-making obtained the highest average (2.88), followed by self-management (2.84), fourth social awareness (2.81). and fifth self-awareness (2.58), all with a grade of medium, while the future skills axis for mathematics teachers obtained a large degree of availability, with an average of 3.49) out of 5. ) Where technical skills came with an average of (3.58) and applied skills with an average of (3.41), the results showed that there were statistically significant differences in social and emotional learning competencies attributed to the gender variable, and in favor of male teachers. While there are no statistically significant differences due to the variables (scientific qualification, years of experience), and there are no statistically significant differences in future skills due to variables (gender, scientific qualification, and years of experience), the results also showed a correlation of (0.251) between the competencies of social and emotional learning and future skills among mathematics teachers, and reflect a relationship weak, and the researchers recommended a set of recommendations, the most important of which are: The Ministry of Education should adopt the holding of courses, workshops and lectures on the competencies of social and emotional learning for mathematics teachers in particular and for teachers in general.
Keywords: Social and Emotional Learning Competencies; Future Skills; Mathematics; Oman